المرأة وإشكالية التمكين الاقتصادي: مراجعة في المفاهيم والاتجاهات المستقبلية - دوش, حمزة; عبد الكريم, معطى الله (جامعة الوادي.University eloued, 2022)
يرتبط تمكين المرأة بالتنمية الاقتصادية ارتباطا وثيقا، حيث أنه لا يمكن للتنمية وحدها أن تلعب دورا رئيسيا في الحد من عدم المساواة بين الرجل والمرأة؛ ومن جهة أخرى قد يفيد تمكين المرأة التنمية، حيث أصبح اليوم الحديث عن المرأة وضرورة تحقيق تمكينها اقتصاديا، على أنه الأرضية الأساسية لبناء مجتمعات واقتصاديات تنافسية ومتينة وبشكل ممتاز؛ ولا تزال المرأة تواجه التميز والتهميش والإقصاء ﻋﻠﻰ الرغم من التقدم الذي أحرزته، عكس ما تنص عليه المبادئ العالمية التي يقرها المجتمع الدولي.من هنا تكمن أهمية وضع الضوابط المساعدة الممكنة للمرأة اقتصاديا بما يحقق مشاركتها في تحقيق التنمية المستدامة من خلال المكانة المنوطة بها اجتماعيا, سياسيا واقتصاديا... ، انطلاقا من تحسين وضع المرأة الاقتصادي على أساس فرضية مفادها أن المرأة شريك أساسي لعملية التنمية الاقتصادية. The empowerment of women with economic development is closely linked, as development alone cannot play a major role in reducing inequality between men and women; On the other hand, the empowerment of women may benefit development, as today there is talk of women and the need to achieve their economic empowerment as the basic ground for building competitive, solid and excellent societies and economies. Women continue to face discrimination, marginalization and exclusion despite the progress they have made, contrary to what is stipulated in the global principles approved by the international community. Hence the importance of setting possible economic assistance controls for women in order to achieve their participation in achieving sustainable development through the status assigned to them socially and politically And economically..., based on improving the economic status of women based on the premise that women are essential partners in the process of economic development.
مجلد 01 العدد 01
Keywords: لسياسات، التمكين الاقتصادي، تمكين المرأة، النمو الاقتصادي; Policies, economic empowerment, empowerment of women, economic growth